Development of generator outage performance index for power system / Wan Shamsuddin Wan Yusoff - Wan Yusoff, Wan Shamsuddin (2003)
Many utilities in the world are limited with regard to security in their routine operation. Moreover, it can be safely stated that security at any utility becomes a limiting factor during cascaded of transmission line relief events and extreme contingencies such generator outage. Generator outage performance index is therefore an important operating function, which is currently performed to identify the severity of the power system during the outage at the certain point of generator. So that the power system will be operated in a secure situation responsive to the awareness of generator outage ai certain bus. Therefore the severity of the system during the occurrence of generator outage can be determined using generator outage performance index.